2021
DOI: 10.1016/j.ultsonch.2021.105659
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic structural modification of myofibrillar proteins from Coregonus peled improves emulsification properties

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 62 publications
4
31
0
Order By: Relevance
“…These results are similar to those of Amiri et al [27] and Zhu et al [13] . In contrast, some studies postulate that HIU processing reduces the R–SH contents of proteins [10] . For example, it has been reported that ultrasound treatment could generate free radicals and superoxide, which oxidize the free R–SH group to form sulfinic and sulfonic acid [25] .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…These results are similar to those of Amiri et al [27] and Zhu et al [13] . In contrast, some studies postulate that HIU processing reduces the R–SH contents of proteins [10] . For example, it has been reported that ultrasound treatment could generate free radicals and superoxide, which oxidize the free R–SH group to form sulfinic and sulfonic acid [25] .…”
Section: Resultsmentioning
confidence: 94%
“…The emulsifying property of the samples was measured as described by Deng et al [10] with minor modifications. The protein samples (3 mg) were homogenized with 27 mL deionized water, followed by emulsification of soy oil and sample solution in a ratio of 1:3 for 2 min using a high-speed homogenizer (CTK 10 K, Brookfield, USA) at 10,000 rpm/min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of whether SDS-PAGE was under reducing or non-reducing conditions, it can be observed that the molecular weight distribution of all samples was similar, which indicated that subunits of the CPI had not changed obviously after ultrasonic modification. This was because that ultrasonic treatment neither broke the original covalent bonds nor induced the formation of new ones [ 30 ]. These results were consistent with some reported researches [ 31 ].…”
Section: Resultsmentioning
confidence: 99%